Konsep Diri dan Konformitas Pada Perempuan Peminat Trend Fashion Coquette di Masa Emerging Adulthood - Syaadah, Syajida Mariam Dadah; Abdillah, Rijal (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Basically the emerging adulthood period is exploratory, because individuals need to support their appearance by adjusting themselves to keep looking trendy and up-to-date, so this research is motivated by the emergence of following fashion trends as a style of dress in order to have similarities with other individuals and their existence can be recognized by the environment. Therefore, it affects their view of themselves. There are factors that influence the occurrence of conformity, one of which is self-concept. Thus, this study aims to see how self-concept can influence individual behavior to adjust themselves when a fashion trend such as coquette appears. This research uses a quantitative method with a type of non-probability sampling, namely accidental sampling as a data collection process involving 100 female respondents who have been collected through distributing google form questionnaires with a Likert scale. Data analysis in this study used the help of IBM SPSS statistical 26 for windows software with results that showed a positive and significant relationship and the influence between self-concept on conformity by 64%, while based on the results of score categorization, the majority of respondents had a moderate level of self-concept and conformity. The results of this study are expected to provide insight into the importance of identifying a style of dress that reflects one's personality and values without having to follow other individuals.